2019
DOI: 10.1002/ptr.6342
|View full text |Cite
|
Sign up to set email alerts
|

The clinical effects of purslane (Portulaca oleracea) seeds on metabolic profiles in patients with nonalcoholic fatty liver disease: A randomized controlled clinical trial

Abstract: Nonalcoholic fatty liver disease (NAFLD) is the most common form of chronic liver diseases associated with unfavorable metabolic profiles and oxidative stress parameters. This study was designed to determine the effects of purslane seeds consumption with a low‐calorie diet on insulin resistance, lipid profile, and oxidative stress indices in patients with NAFLD. This randomized controlled clinical trial was conducted on 54 individuals with NAFLD. Subjects were randomly assigned to consume either 10 g/day of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 55 publications
3
50
0
1
Order By: Relevance
“…To our knowledge, this study is the first randomized, double-blind clinical trial, which has assessed the effects of purslane extract on NAFLD characteristics. In fact, previous clinical trials assessing the effects of purslane, have focused on the effects of purslane seeds rather than purslane extract (Dehghan et al, 2016;El-Sayed, 2011;Esmaillzadeh et al, 2015;Gheflati et al, 2019). Our results demonstrated that 300 mg/day of purslane extract supplementation, had no effect on lipid profile, glycemic indices and liver enzymes.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…To our knowledge, this study is the first randomized, double-blind clinical trial, which has assessed the effects of purslane extract on NAFLD characteristics. In fact, previous clinical trials assessing the effects of purslane, have focused on the effects of purslane seeds rather than purslane extract (Dehghan et al, 2016;El-Sayed, 2011;Esmaillzadeh et al, 2015;Gheflati et al, 2019). Our results demonstrated that 300 mg/day of purslane extract supplementation, had no effect on lipid profile, glycemic indices and liver enzymes.…”
Section: Discussionmentioning
confidence: 54%
“…Then, a balanced diet, providing about 500 kcal/day less than the total daily energy requirement (15% protein, 55% carbohydrate, and 30% fat), was calculated and prescribed for each patient. The percentage of macronutrients was in accordance with the recommendations for NAFLD (Gheflati, Adelnia, & Nadjarzadeh, 2019;Jeznach-Steinhagen et al, 2019). The minimum calculated energy for weight reduction was about 1,300 kcal.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Using Stata software, considering alpha 5%, power 90%, and based on Gheflati et al [ 39 ] studying that the mean of LDL was 120.8 standard deviation (SD = 24.8) in the intervention group (purslane seeds) and 148.4 (SD = 35.8) in the control group, the required sample size in each group was estimated to be 27 cases; considering the probability of attrition, 37 cases were calculated for each group. By expanding this sample size to the number of groups, 74 cases were entered into the study.…”
Section: Methodsmentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a common chronic disease characterized by the accumulation of fat in the liver, which can be associated with obesity, and can progress to brosis, cirrhosis, and even liver cancer [1].NAFLD is considered as an important feature of metabolic syndrome and an important factor causing cardiovascular diseases. More studies have suggested that NAFLD is related to male sexual dysfunction and reproductive dysfunction [2].NAFLD has also been shown to be associated with poor metabolism and oxidative stress [3].Other studies have linked NAFLD to sedentary behavior and poor eating habits [4].NAFLD is one of the most common chronic liver diseases in developed countries [5]. Except for lifestyle intervention, no drugs are currently approved for the treatment of NAFLD, so more clinical studies are needed to nd new methods for the treatment and management of NAFLD.…”
Section: Introductionmentioning
confidence: 99%